The Use of Padlet in Supporting Creativity and Interaction among Peers - Rosnani, Ismail; Noraisah Nurul Fatwa, Mohd Razali (UPM, 2022)
The COVID-19 pandemic posed challenges to the learning process, such as unstable internet connectivity, which affected online teaching and learning. To maintain student engagement, alternative educational tools like Padlet have been utilized to facilitate English language learning, leveraging its interactive features to address teaching challenges and enhance student participation and creativity. This study aims to examine the effectiveness of Padlet in fostering creativity and encouraging peer interaction during English language learning sessions. Conducted over 14 weeks with 84 students, the research utilized Padlet for activities like information sharing, assignments, and peer feedback. Data was collected through questionnaires and analysed using thematic analysis to identify themes related to creativity and interaction. Findings indicate that Padlet supports creativity by inspiring new ideas, revealing hidden talents, and developing skills in technology and critical thinking. It also facilitated information sharing, improved comprehension, and fostered a supportive and engaging learning environment. The study suggests that integrating innovative tools like Padlet in education can significantly enhance teaching outcomes, boost student engagement, and make learning more interactive, encouraging educators to incorporate such technologies to create meaningful and dynamic learning experiences.